Global ischemic heart disease burden attributable to environmental risk factors, 1990–2021: an Age-Period-Cohort analysis - Su, Rui; Ze, Wangchu; Huang, Ruiyu; Guo, Yanxia; Liu, Gang; Zhang, Baolu (Frontiers in Public Health, 2025)
BackgroundIschemic heart disease (IHD) is the leading cause of global deaths. Environmental exposures contribute substantially to IHD burden, yet their combined effects across socio-demographic strata remain poorly characterized.ObjectiveThis study aimed to systematically evaluate the global burden of IHD attributable to environmental factors, analyzing its temporal trends, geographical patterns, and Age-Period-Cohort (APC) effects across different socio-demographic index regions from 1990 to 2021.MethodsData for this study were obtained from the Global Burden of Disease 2021 (GBD 2021) public dataset to investigate age-standardized deaths rates and disability-adjusted life years (DALYs) rates of IHD attributable to environmental factors from 1990 to 2021. Environmental factors included particulate matter pollution, non-optimal temperature, and lead exposure. Countries were categorized into five socio-demographic index (SDI) levels. The APC analysis model was employed to disentangle age, period, and cohort effects. Data processing and visualization were conducted using R version 4.4.3.ResultsBetween 1990 and 2021, global environmental IHD deaths rates decreased by 31.13% and DALYs rates by 29.85%. High SDI regions achieved 70.39% reduction in deaths rates, while low SDI regions showed only 3.13% decrease. Particulate matter pollution remained the predominant environmental contributor with the highest burdens in South Asia, the Middle East, and North Africa. APC analysis revealed that environmental-related IHD burden increased exponentially with age, with earlier birth cohorts showing substantially higher Risk Ratios (RR). Males consistently demonstrated higher burden than females across all environmental factors.ConclusionIHD burden attributable to environmental factors shows a declining trend globally but with notable regional and gender disparities. Policymakers in low SDI regions should integrate environmental health into development strategies, high-pollution burden regions should strengthen air quality monitoring and emission control, climate-sensitive regions need to implement temperature adaptation planning, and historically industrialized regions should enhance lead exposure monitoring while ensuring occupational protection for males and environmental health safeguards for the older adults.